BASES AND ANALYSIS OF EVALUATION OF INNOVATION POTENTIAL OF INDUSTRIAL ENTERPRISES (Scientific Journal of Actuarial Finance and Accounting, 2022)
The article presents the theoretical and methodological basis for assessing the innovative potential of industrialenterprises and the study of the acceptability of the introduction of strategic management methods in the development ofthe innovative environment of corporate structures in the context of economic liberalization.